How In-Group Bias Influences Source Memory for Words Learned From In-Group and Out-Group Speakers - Iacozza, Sara; Meyer, Antje S.; Lev-Ari, Shiri (Frontiers in Human Neuroscience, 2019)
Individuals rapidly extract information about others’ social identity, including whether or not they belong to their in-group. Group membership status has been shown to affect how attentively people encode information conveyed by those others. These findings are highly relevant for the field of psycholinguistics where there exists an open debate on how words are represented in the mental lexicon and how abstract or context-specific these representations are. Here, we used a novel word learning paradigm to test our proposal that the group membership status of speakers also affects how speaker-specific representations of novel words are. Participants learned new words from speakers who either attended their own university (in-group speakers) or did not (out-group speakers) and performed a task to measure their individual in-group bias. Then, their source memory of the new words was tested in a recognition test to probe the speaker-specific content of the novel lexical representations and assess how it related to individual in-group biases. We found that speaker group membership and participants’ in-group bias affected participants’ decision biases. The stronger the in-group bias, the more cautious participants were in their decisions. This was particularly applied to in-group related decisions. These findings indicate that social biases can influence recognition threshold. Taking a broader scope, defining how information is represented is a topic of great overlap between the fields of memory and psycholinguistics. Nevertheless, researchers from these fields tend to stay within the theoretical and methodological borders of their own field, missing the chance to deepen their understanding of phenomena that are of common interest. Here we show how methodologies developed in the memory field can be implemented in language research to shed light on an important theoretical issue that relates to the composition of lexical representations.